IMPLEMENTATION OF E-GOVERNMENT IN DIGITALIZATION OF ARTS AND CULTURE AT UPT TAMAN BUDAYA OF EAST JAVA PROVINCE - Anggrainie, Noni Triyana (MAP Observer: Jurnal Penelitian Administrasi Publik, 2024)
The development of technology, especially digital media, has also advanced the development of information and communication, this has made several government policies prioritize the development of digital information, one of which is in the field of arts and culture. UPT Taman Budaya Jawa Timur has begun to explore documentation and presentation using digitalization methods by using the role of social media, so that virtual presentations in the context of digitalization of arts and culture need to be managed properly. This study uses a descriptive qualitative method that refers to the results of interviews with informants and examines documents and broadcasts related to the research. The results of the study show that the role of digitalization in arts and culture at UPT Taman Budaya Jawa Timur has a positive influence and shows developments towards a better direction in order to preserve and develop arts and culture as a heritage and identity of the Indonesian Nation.